Adoption of e-learning among instructors in higher institutions in Nigeria: A case study of Obafemi Awolowo University, Ile-Ife, Nigeria - Oyeleke Oluniyi; Tomilola Taiwo Apena (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
The study investigates the attitude of faculty members towards the adoption of the e-learning among instructors in Obafemi Awolowo University, Ile-Ife, Nigeria. It also investigates instructors' preference for face-to-face, full online and blended approach. Sixty six faculty members whose departmental courses were among the first set of course to be mounted online were used for the study. An adapted and validated questionnaire instrument was used to obtain data from the respondents. The results show that 43.1 percent of the respondents would want to adopt e-learning, while 13.8 percent shows a negative disposition, and 43 percent were neutral. In preference among online, blended, and face-to-face; 40 percent would prefer face-to-face, 41.5 would prefer online, while 50.7% would prefer a blended approach. Out of those who prefer blended approach, 63.7% prefer 70% online, 30% face-to-face; 42% prefer 40% online, 60% face-to-face; and 33.3% prefers 50% online, 50% face-to-face. The results show that instructors have positive disposition towards adoption of e-learning, but there is load of skepticism as reflects in high number of respondents who chose a neutral option. Though there seems to be positive disposition to adoption, blended approach seems to be a preferred option than full online. Finally, there is no significant difference in their attitude towards adoption of e-learning in terms of gender and age.
Keywords: 650; Attitude; Adoption; E-learning; Blended Learning